Importance Of Body Donation In Rachna Sharir- A Review Study - Tawde, Kirtibala; Wane, Yogesh; Joshi, Prakash (International Research Journal of Ayurveda & Yoga, 2020)
Rachna sharir is a subject of Ayurveda, which deals with the structures and its particular functions. Rachna word itself meaning is the structure. According to some Acharyas “Rachna adikratyamkratamtantramrachanashariram” it means Shastra related to Rachna is Rachna Sharir. In modern medical science Rachna Sharir correlated with anatomy but there is some difference between them. Anatomy is one of the most important subject and course for education and knowledge of whole body grossly or subtly through dissection Every medical student, who want to know about the internal and external structure of the human body must read anatomy and do dissection on cadaver. Vesalius Andrious wrote in the preface of his ‘De fabrica’ (1543)- Anatomy should rightly be regarded as the firm foundation of the whole art of the medicine and its essential preliminary for study of anatomy of human body the dissection is a must. Dissection means the process of cutting apart or separating tissue, in order to study its structures. For study or dissection we need an unclaimed body or cadaver. Some people donate their body on their own volition or wish and for educational help it’s a great work. Body donation, anatomical donation or body bequest is the donation of undamaged body after death for research and educational purpose. Donated bodies are used for the research and educational use. Usually there is no cost in donation of body to science. If any person wants to donate their body may go through a willed body donation and the bodies are used for enhance the knowledge of human being that is helpful for anatomy student for his future and education support.